Laboratory and genetic predictors for severe COVID-19 infection - Tanya Kadiyska; Radostina Cherneva; Zheina Cherneva; Sotir Marchev; Dilyana Madzharova; Ivan Tourtourikov; Vanyo Mitev (Pensoft Publishers, 2024)
This study aims to identify laboratory and genetic markers important for COVID-19 severity to improve patient assessment and treatment. COVID-19 patients were divided into two groups based on disease severity. Clinical, laboratory (complete blood count, complete biochemical parameters - lactate dehydrogenase (LDH), serum ferritin), and genetic markers (OAS1 rs4767027) were analyzed. A total of 61 COVID-19 patients and 48 negative controls were investigated. Group I showed more often lymphopenia - 3.16 (1.39-3.89) vs 5.61(4.21-7.98), p-0.027 and thrombocytopenia - 165 (75-256) vs 212 (198-349), p-0.031, higher LDH (621 ± 218 U/L vs 312 ± 110 U/L), p-0.014. OAS1 rs4767027 genotype and allele frequencies did not differ significantly from worldwide population frequencies. Lymphopenia and thrombocytopenia are likely associated with immune inflammation and COVID-19 severity. While increased OAS1 transcript levels are correlated with reduced risk of infection, they can contribute to NLRP3 inflammasome activation once the infection has been established.